Dynamics of the two-SBT-memristor-based chaotic circuit*Project supported by the National Natural Science Foundation of China (Grant Nos. 61703247 and 61703246), the Qingdao Science and Technology Plan Project, China (Grant No. 19-6-2-2-cg), the Elite Project of Shandong University of Science and Technology, and the Taishan Scholar Project of Shandong Province of China. (November 2020) - Guo 郭, Mei 梅; Zhang 张, Meng 萌; Dou 窦, Ming-Long 明龙; Dou 窦, Gang 刚; Li 李, Yu-Xia 玉霞
Abstract : A two-SBT-memristor-based chaotic circuit was proposed. The stability of the equilibrium point was studied by theoretical analysis. The close dependence of the circuit dynamic characteristics on its initial conditions and circuit parameters was investigated by utilizing Lyapunov exponents spectra, bifurcation diagrams, phase diagrams, and Poincaré maps. The analysis showed that the circuit system had complex dynamic behaviors, such as stable points, period, chaos, limit cycles, and so on. In particular, the chaotic circuit produced the multistability phenomenon, such as coexisting attractors and coexisting periods.